Theoretical approaches to e-book research (Libellarium: journal for research in the field of information and related sciences, 2016)
The adoption and continued use of innovations by societies, organisations and individuals has been a subject of research since before the 1930s. A variety of different theories have been developed to account for the different speeds at which innovations are adopted and the factors that affect the adoption process. This paper reviews theories of the adoption of innovations with particular reference to the recent phenomenon of the e-book as a cultural innovation that is having an impact on individuals, organizations and national policy makers. The paper will suggest which theories are most appropriate for the different levels at which the innovation is employed.
Keywords: e-book; theories of the adoption of innovations